Meretas Akar Konflik dan Kekerasan: Refleksi Protestan - Albertus Patty (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
More than half of the violence and warfare in this world are actually motivated and justified by religion! Therefore, how can religion become a catalyst for peace amidst this culture of violence and warfare? The peace referred to here is a situation where everyone can enjoy freedom, justice, equality, and brotherhood with one another. The root of conflict and violence among various religious communities arises from both theological and non-theological issues. Among these sources, the main one is the unpreparedness of religious communities to live in a multicultural society and world. When rationality fails to realize its vision in building a civilization full of peace, religion is once again challenged to prove its prophetic role in creating peace in this world. Thus, dialogue becomes crucial in building that peace, but it must be placed within a soteriological framework, namely salvation: the salvation of humanity which includes freedom, justice, equality, peace, and the salvation of the earth and this planet. Dialogues like this certainly enrich and become a blessing for all creatures.